Learning about Variable Demand in the Long Run - Aldo Rustichini; Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
This paper studies the problem of a monopoly who is uncertain about the demand it faces and learns about it over time through its pricing experience. The demand curve facing the monopoly is not constant–it changes over time in how it differs from an informed monopoly's policy. It turns out that, even when the rate at which the demand varies is negligible, the stationary probability with which the monopoly's policy deviates from its informed counterpart is non-negligible, as long as the discount factor is below 1.
Keywords: 330